School Climate and Teacher Attrition Intentions: A Case Study of Junior High Schools in Bole District, Ghana - Kanyiri, Agape (Journal of Social and Scientific Education, 2025)
Scholars have often alluded to factors influencing teacher attrition rates in schools, including inadequate compensation, limited career progression, excessive workload, lack of professional development, and poor work-life balance. Yet, the extent to which a hostile school climate prompts teacher attrition or, at the very least, attrition intentions has received relatively little attention. This study explores this gap by examining the relationship between school climate and teacher attrition intentions in the Bole District of Ghana. Data were collected from teachers and head teachers through interviews and focus group discussions, supplemented by a review of transnational discourse on school climate and teacher attrition. Using inductive thematic analysis, the study identified a distinctly hostile school climate in Bole’s Junior High Schools, characterized by authoritarian leadership, a lack of collegial support, exclusion based on ethnicity, religion, or political affiliation, and prevalent student indiscipline. While actual attrition levels were low—primarily due to limited alternative employment opportunities, transfer difficulties, and teachers’ reluctance to separate from their families—attrition intentions were high, fueled by the persistent hostility within the school environment. The study posits that a hostile school climate significantly increases the risk of teacher attrition by eroding job satisfaction and professional well-being. To mitigate these risks, the study recommends the adoption of participatory leadership approaches, the promotion of inclusivity in school environments, and the establishment of effective disciplinary measures to foster a more supportive and cohesive climate conducive to teacher retention and student success.